2017
DOI: 10.5935/0004-2749.20170025
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of phacoemulsification in patients with uveitis at a tertiary center in São Paulo, Brazil: a review of cases from 2007 to 2012

Abstract: Phacoemulsification with IOL implantation improved vision in most patients with coexisting cataracts and uveitis. Good preoperative and postoperative control of inflammation plays an important role in achieving favorable visual outcomes. Furthermore, the final visual outcome depends on the posterior segment status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
1
5
1
3
Order By: Relevance
“…Prolonged eye inflammation after surgery is relatively rare, especially if heparin-surface-modified intraocular lenses are implanted [ 8 ]. Postoperative rising of intraocular pressure can occur frequently in these patients [ 2 , 9 ]. Good preoperative and postoperative control of inflammation plays an important role in achieving favorable visual outcomes [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged eye inflammation after surgery is relatively rare, especially if heparin-surface-modified intraocular lenses are implanted [ 8 ]. Postoperative rising of intraocular pressure can occur frequently in these patients [ 2 , 9 ]. Good preoperative and postoperative control of inflammation plays an important role in achieving favorable visual outcomes [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative rising of intraocular pressure can occur frequently in these patients [ 2 , 9 ]. Good preoperative and postoperative control of inflammation plays an important role in achieving favorable visual outcomes [ 9 , 10 ]. Visual outcome is generally good, but poorer than in non-uveitis eyes [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have demonstrated the safety and efficacy of IOL implantation at the time of surgery in patients with uveitis with a low risk of complications, as long as the inflammation is well controlled. [ 41 42 43 44 45 ] However, in patients with chronic uncontrolled uveitis such as JIA uveitis, IOL implantation should be deferred. Alió et al .…”
Section: Ntraoperative C Onsiderationsmentioning
confidence: 99%
“…Moorthy e colaboradores (190) relataram que 68% dos 19 olhos submetidos à cirurgia de catarata evoluíram com uma acuidade visual de 20/40 ou melhor. Cerqueira e colaboradores (191) avaliaram os resultados da facectomia em pacientes com uveíte em um hospital terciário.…”
Section: Complicaçõesunclassified
“…Foram avaliados 45 olhos de 38 pacientes, dos quais nove olhos eram de pacientes portadores da DVKH. A maioria dos olhos pós-facectomia apresentou melhora de acuidade visual em relação ao quadro inicial (191) .…”
Section: Complicaçõesunclassified